2017
DOI: 10.1016/j.ctro.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms might influence chemotherapy induced nausea in women with breast cancer

Abstract: BackgroundWomen receiving FEC (5 fluorouracil, epirubicin and cyclophosphamide) chemotherapy (CT) for breast cancer (BC) often experience side effects such as nausea and vomiting. Individual variations of side effects occur in patients despite similar cancer therapy. The purpose of this study was to investigate a possible genetic background as a predictor for individual variations in nausea induced by CT.Methods114 women were included in the study. All women received adjuvant CT for BC. Self-reported nausea an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
12
1
Order By: Relevance
“…This indicates the impact CINV had on the daily life of these women. The study showed that most women estimated CINV with great variety and some of the women did not follow the pattern from other studies [58,118].…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…This indicates the impact CINV had on the daily life of these women. The study showed that most women estimated CINV with great variety and some of the women did not follow the pattern from other studies [58,118].…”
Section: Discussioncontrasting
confidence: 58%
“…Antiemetic management is stated by a guideline from the Southeastern health region in Sweden based on the American Society of Clinical Oncology antiemetic guideline [57]. Despite all new drugs, nausea remains a clinical problem [58,59] (Table 1).…”
Section: Mechanism Of Nauseamentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing colorectal neoplasia, a statistically significant difference was observed for the symptom of nausea when compared to breast neoplasia. Different results were found in the study of Oliva, et al (21) in Sweden between chemotherapy treatment in women with breast cancer and who exhibited prevalent symptom of nausea (21) .…”
Section: Discussionmentioning
confidence: 79%
“…The complete pathophysiology of CINV is not known but gastrointestinal (GI) side effects associated with anticancer chemotherapy are traditionally thought to be attributable to mucosal damage [ 23 ]. Nausea is complex in nature and probably depending on more than one etiological factor [ 24 ]. Different pathways have been identified for acute and delayed CINV [ 25 ].…”
Section: Introductionmentioning
confidence: 99%